Efeitos da formulação mucoadesiva contendo os extratos de Curcuma longa L. (Zingiberaceae) e Bidens pilosa L. (Asteraceae) no tratamento da mucosite oral: estudos não clínicos e clínico fase I - Santos Filho , Edvande Xavier dos (2018)
Mucositis is one of the main side effects in antineoplastic therapies, in which reactive oxygen species (ROS), second messengers, upregulation of pro-inflammatory cytokines and metabolic byproducts of colonizing microflora are all involved. This serious limiting side effect is observed at a rate of 40–100% in patients and despite different palliative measures and therapeutic agents have been investigated, still no therapy was completely successful. Preclinical repeated-dose toxicity and efficiency studies developed by our group have suggested the potential of the mucoadhesive formulation containing curcuminoids and Bidens pilosa L. extract (FITOPROT) in treating mucositis. Therefore, in the current approach we aimed to evaluate the effects of FITOPROT as a protective agent against 5-fluorouracil (5-FU)-induced cellular toxicity using a cell line model of mucositis; and establish the safety and recommended phase II dose of FITOPROT for the prevention and treatment of chemoradiotherapy-induced oral mucositis (OM) in patients with head and neck cancer. In the non-clinical (in vitro) study, HaCaT cells were pretreated with 0.005% of FITOPROT for 24 hours, and then exposed concomitantly with FITOPROT and 5-FU (10 μg/mL) for more 24 hours. Oxidative stress, mitochondrial membrane potential, inflammatory levels, apoptosis, antioxidant response and cellular proliferation were evaluated. In the presence of 5-FU, FITOPROT significantly reduced ROS generation, avoided mitochondrial membrane depolarization and cellular proliferation loss; modulated oxidant response, apoptosis and inflammation by reducing respectively Nrf2, TNF, cytochrome c, NF-κB and pro-inflammatory cytokines (IL-1β, IL-6, IL-8) levels. In the phase I study, twenty healthy adult participants were randomized into two groups that received different pre-established concentrations of the collutory. Participants rinsed their mouths with FITOPROT, three times daily, for ten consecutive days. Safety assessments included identification of potential discomfort and/or local adverse reactions (CTCAE v5.0), and chemistry laboratory tests (hematologic, hepatic, renal and glycemic evaluation). Furthermore, genotoxic effects in exfoliated oral mucosal epithelial cells; biochemical analyses including salivary myeloperoxidase, malondialdehyde and nitric oxide concentration; and salivary cytokine levels were investigated. No participant experienced toxicity or unacceptable discomfort and/or adverse reactions during FITOPROT use, with laboratory and clinical parameters under normal conditions. The only side effects observed were low intensity and temporary mucosa/dental surface pigmentation (n=7) and tooth sensitivity (n=4), which disappeared after the use of formulation ceased. No significant cellular genotoxic effects were observed, and micronuclei frequencies were not changed (P>0.05). Biochemical assays reveled no altered levels of myeloperoxidase (P=0.2268), malondialdehyde (P=0.1188) nor nitric oxide (P=0.5709) concentration, and no significant difference were found in the levels of pro-inflammatory cytokines (P>0.05) in saliva during both FITOPROT tested doses use. As conclusion, it could be seen FITOPROT protected HaCaT cells against 5-FU-induced damage exerting chemoprotective activity; and FITOPROT demonstrated to be safe and tolerable in both tested doses, been suitable for evaluation in a phase II trial as treatment against oral mucositis.